2021
DOI: 10.1002/uog.23141
|View full text |Cite
|
Sign up to set email alerts
|

Elective labor induction vs expectant management of pregnant women at term and children's educational outcomes at 8 years of age

Abstract: Objective To estimate the effect of elective induction of labor at 39 weeks' gestation on children's educational outcomes as measured using the Australian National Assessment Program—Literacy and Numeracy (NAPLAN) tests in school year 3 (∼8 years of age), compared with expectant management. Methods We merged perinatal data on all infants born in South Australia from 1999 to 2008 with children's school assessment data from NAPLAN. The study population included all singleton infants born without a malformation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(38 reference statements)
1
4
0
2
Order By: Relevance
“…A large retrospective cohort study from Scotland demonstrated a step-wise decrease in the probability of special education needs with advancing gestation, a trend that extended into postterm gestations. 5 Recent cohort studies have concluded that those born electively at 39 or 40 weeks' gestation had similar year 3 school performance outcomes compared with those born following expectant management (from Australia, where 1353 were induced at 39 weeks' gestation 6 ; and Rhode Island, where 455 were induced at 39 or 40 weeks' gestation 7 ). To our knowledge, no large cohort studies have examined the impact of inducing birth at 39 weeks' gestation on global childhood developmental outcomes beyond educational performance, such as social competency, emotional maturity, and communication skills.…”
mentioning
confidence: 99%
“…A large retrospective cohort study from Scotland demonstrated a step-wise decrease in the probability of special education needs with advancing gestation, a trend that extended into postterm gestations. 5 Recent cohort studies have concluded that those born electively at 39 or 40 weeks' gestation had similar year 3 school performance outcomes compared with those born following expectant management (from Australia, where 1353 were induced at 39 weeks' gestation 6 ; and Rhode Island, where 455 were induced at 39 or 40 weeks' gestation 7 ). To our knowledge, no large cohort studies have examined the impact of inducing birth at 39 weeks' gestation on global childhood developmental outcomes beyond educational performance, such as social competency, emotional maturity, and communication skills.…”
mentioning
confidence: 99%
“…The results of a large randomized controlled trial concerning the clinical benefit of induction of labor at term (ARRIVE study: A Randomized Trial of Induction Versus Expectant Management) indicate that in primipara without relevant risk factors an elective induction of labor from 39 + 0 weeks of gestation (WG) may lower the caesarean section rate without negatively influencing the perinatal outcome [16]. Furthermore, a recent study of a large number of cases (n = 53 843) was able to demonstrate that the elective induction of labor from 39 + 0 WG did not seem to have an influence on the childʼs school performance at an age of 8 years [17]. Recently, an increased rate of IUFD could be observed when exceeding the delivery date and prolongating beyond 41 + 0 WG (SWEPIS study: SWEdish Post-term Induction Study), although methodological limitationsparticularly those concerning the heterogeneity of the study populationneed to be considered [18].…”
Section: Induction Of Labormentioning
confidence: 99%
“…The currently available results concerning fetomaternal Doppler ultrasound in the low-risk population (AGA fetuses) and its association with an APO, in particular in late-term cases, raise the question of whether abnormal Doppler indices can or even should be cause for clinical consequences (even in the case of physiological amniotic fluid volume and CTG). Taking into account the current data around the added value of induction of labor in the low-risk population at term or late term 16 , 17 , 18 , anomalies in the established fetomaternal Doppler indices should give rise to the consideration of whether the recommended offer of induction of labor at 41 + 0 20 in the S3 guideline should be a recommendation instead of an offer. At the very least, the authors believe that – if the fetomaternal Doppler ultrasound is properly used as part of the fetal monitoring in the low-risk population – an appropriate patient education and a participative form of decision-making should be employed when deciding on the timing of induction of labor during the late-term period.…”
Section: Fetomaternal Doppler Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations